1994
DOI: 10.3109/03005369409086577
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic distortion products (ADP) from the ears of term infants and young adults using low stimulus levels

Abstract: It has been shown previously that relatively low stimulus levels (L1 = 55, L2 = 40 dB SPL) elicit recordable levels of ADP from healthy adult ears (Gaskill and Brown, 1990). We have used the same stimulus levels in healthy term infants within 6 days of birth. The results from the 38 infants who provided data from both ears (from a total of 66 attempted) are reported here. The data were compared with those from 12 adults aged 20 to 30 years with normal audiometric thresholds. ADP was measured across frequency w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 23 publications
2
12
1
Order By: Relevance
“…There is evidence to suggest that infants and children may have DPOAE of greater amplitude than adults (Dorn et al, 1998;Brown et al, 1994;Prieve et al, 1997). These effects are small, however, and do not reach statistical signi cance in many of the studies.…”
Section: Introductionmentioning
confidence: 84%
“…There is evidence to suggest that infants and children may have DPOAE of greater amplitude than adults (Dorn et al, 1998;Brown et al, 1994;Prieve et al, 1997). These effects are small, however, and do not reach statistical signi cance in many of the studies.…”
Section: Introductionmentioning
confidence: 84%
“…Brown et al ͑1994͒ reported that DPOAE levels in neonates were approximately 10 dB higher than they were in a group of adults for f 2 frequencies ranging from 1000 to 8000 Hz, but only the difference at the f 2 frequency of 1000 Hz was significant. Bergman et al ͑1995͒ also reported that DPOAE levels measured from graduates of the neonatal intensive care unit ͑NICU͒ and term neonates were higher than those from a group of older children and adults across a broad frequency span, but did not indicate whether these differences were statistically significant.…”
Section: Introductionmentioning
confidence: 86%
“…A decade of work from various laboratories has found that DPOAE-based measures of cochlear function are not completely adult-like in human infants ͑Brown et al, 1994;Lasky, 1998;Abdala, 2001b. Brown and colleagues ͑1994͒ reported immature cochlear filtering in newborns at 4000 Hz, as measured by DPOAE f 2 / f 1 -ratio functions.…”
Section: A Dpoaes To Study Maturation Of Auditory Peripheral Functionmentioning
confidence: 96%